1995
DOI: 10.1093/bja/75.5.562
|View full text |Cite
|
Sign up to set email alerts
|

Manual compared with target-controlled infusion of propofol

Abstract: We studied 160 ASA I-II patients, anaesthetized with propofol by infusion, using either a manually controlled or target-controlled infusion system. Patients were anaesthetized by eight consultant anaesthetists who had little or no previous experience of the use of propofol by infusion. In addition to propofol, patients received temazepam premedication, a single dose of fentanyl and 67% nitrous oxide in oxygen. Each consultant anaesthetized 10 patients in sequential fashion with each system. Use of the target-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 9 publications
5
69
1
3
Order By: Relevance
“…A commonly used technique involves the induction and maintenance of anaesthesia with propofol, which is associated with a rapid recovery and a low incidence of postoperative nausea and vomiting (PONV). Nevertheless, manual infusions of propofol are difficult to control intra-operatively, resulting in poor surgical conditions [1] and frequent patient movements [2,3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A commonly used technique involves the induction and maintenance of anaesthesia with propofol, which is associated with a rapid recovery and a low incidence of postoperative nausea and vomiting (PONV). Nevertheless, manual infusions of propofol are difficult to control intra-operatively, resulting in poor surgical conditions [1] and frequent patient movements [2,3].…”
mentioning
confidence: 99%
“…This problem has led to the development of computer-assisted or target-controlled infusion (TCI), and such a system for propofol is now commercially available (Diprifusor®). This system has been shown to be easier to use and to result in improved anaesthetic control compared with manual infusion regimens [2,6]. Although it is often claimed that the TCI system is as simple to use as an anaesthetic vaporiser, this claim has not been evaluated in adult patients.…”
mentioning
confidence: 99%
“…Разработаны несколько руководств по схемам введе ния для гипнотиков и опиоидов, например схема Ро бертса для пропофола [3]. Установленная определенная скорость инфузии подходит только для 50 % пациентов [4,5]. Даже если этот единственный факт рассматри вать, он неоспоримо говорит в пользу ИЦК.…”
Section: адрес для корреспонденции (Correspondence Address)unclassified
“…Moreover, the α-adrenergic blockage caused by methotrimeprazine may lead to hypotension by vasomotor regulation decrease 11 . Due to the respiratory depression as a consequence of propofol and opioids affinity to µ receptor and indications for the use of O 2 supplementation during anesthesia, when utilizing these drugs 12 , the use of controlled ventilation in all animals of both groups was indicated in order to assure a good ventilation maintenance by providing a 100% oxygen concentration aiming at keeping ETCO 2 between 35 and 45 mm Hg. There was no alteration in f which remained stable at all moments.…”
Section: Emg (%) Gi Giimentioning
confidence: 99%
“…As for the anesthetic volume, another study, on the contrary, showed a greater propofol consumption when using the target-controlled infusion technique as compared to the steady-speed infusion. However, the flexibility and easy use of this technique (target) encouraged the authors of this work to deepen the anesthesia levels, leading to a greater anesthetic volume consumption 12 , however a certain care has to be taken.…”
Section: Emg (%) Gi Giimentioning
confidence: 99%